Pengaruh Penggunaan Media Pembelajaran Interaktif Terhadap Pemahaman Matematika Dasar di MIN 7 Tapteng - Dinda Rahmadani Simanullang; Dea Aulia Futachi; Lathifah Thuhri Herwana Nasution; Khotna Sofiyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the influence of interactive learning media on basic mathematics understanding in MIN 7 Tapteng. Interactive media in mathematics education such as simulations, animations, and educational games allow for a more interesting and fun way of learning so as to increase learning motivation. This type of research is quantitative research using the experimental method. The population in this study is all grade I students in MIN 7 Tapteng and the sample is 30 students. The research instrument used is a written test in the form of a description. Meanwhile, the data analysis techniques used are normality test, homogeneity test and hypothesis test. The results of the study show that there is an influence of interactive learning media on basic mathematics understanding in MIN 7 Tapteng. This can be seen from the average score of the pretest is 49.2 and the average score of the posttest is 72.6. Based on these results, there is a significant increase in the understanding of Basic Mathematics in MIN 7 Tapteng by applying interactive learning media. Then based on the calculations carried out using the t-test, it shows that the tcount > ttable is 9.78 > 2.048. From the test criteria, Ha is accepted, meaning that there is an influence of interactive learning media on basic mathematics understanding in MIN 7 Tapteng.